Democracy and consensus decision-making among the Bemba-speaking people of Zambia: An African theological perspective - Muwowo, Simon (HTS teologiese studies, 2016)
This article contributes to a critical assessment of the concept of democracy and consensus decision-making of the Bemba matrilineal governance system as a basis for a democratic model of engagement in African politics from an African theological perspective. It is of the opinion that assessing the concept of democracy by consensus decision-making of the Bemba provides a dialogue between the African traditional governance systems as a viable form of political governance ideal for multi-ethnic countries such as Zambia. This is a pinnacle of the 21st century debate which elaborates the important task of African Christian Theology in the rehabilitation, or renovation process of politics of identity for an authentic governance system with authentic African flavour for African governance systems.